Jobshop-Like Queueing Systems - Jackson, James R. (Management Science, 1963)
The equilibrium joint probability distribution of queue lengths is obtained for a broad class of jobshop-like “networks of waiting lines,” where the mean arrival rate of customers depends almost arbitrarily upon the number already present, and the mean service rate at each service center depends almost arbitrarily upon the queue length there. This extension of the author's earlier work is motivated by the observation that real production systems are usually subject to influences which make for increased stability by tending, as the amount of work-in-process grows, to reduce the rate at which new work is injected or to increase the rate at which processing takes place.